Importance of Standards in Biomedical Device and Its Role in Strengthening the Healthcare Sector - Sumana, Gajjala; Rajesh,; Aswal, D. K. (Frontiers in Nanotechnology, 2021)
Biomedical Metrology group of CSIR-NPL (Council of Scientific and Industrial Research—National Physical Laboratory), India is contributing significantly for establishing National Biomedical equipment standardswhich are traceable to primary standards to cater the quality control regulation in Health sector. This initiative has great impact on the health policy and Nation's economy as well. The laboratory has recently established biomedical equipment standard facility and disseminated the services to Industries, stake holders, hospitals and accredited laboratories. Although, the laboratory is successfully providing biomedical equipment calibration services for last 2 years, the sensitization of the information on the recently established metrological capabilities is required, which has great implications in implementation of India's New medical Device rule 2017 effectively. The present paper describes the summary on the significant achievements and role of National Physical Laboratory in supporting the Indian medical device regulations.